2018
DOI: 10.2528/pierl18070302
|View full text |Cite
|
Sign up to set email alerts
|

Using Homogeneous Equivalent Parameters in Finite Element Models of Curved Metamaterial Structures

Abstract: We report on the experimental verification of the employment of equivalent parameters in a 2D finite element model to describe absorptivity of curve-shaped, large-scale metamaterial structures. Equivalent homogeneous optical parameters were retrieved from experimental measurements of flat metamaterial sheets with square resonators of 8 and 9 mm and used in a 2D FE model to obtain the absorptivity of curved structures with similar metamaterial unit cells. The curved structures were experimentally characterized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…Lower conductivity (0.862 S/m) than metal conductors may have contributed to the widening of the absorption curves, providing a greater band of frequency absorption. Larger square arrangements showed absorption bands at lower frequencies, as seen in previous work [ 15 , 18 ]. In addition, as observed experimentally in THz band [ 18 ], the model shows a decrease in absorption magnitude as the square dimensions (and resonant frequency) decrease, everything else being constant.…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…Lower conductivity (0.862 S/m) than metal conductors may have contributed to the widening of the absorption curves, providing a greater band of frequency absorption. Larger square arrangements showed absorption bands at lower frequencies, as seen in previous work [ 15 , 18 ]. In addition, as observed experimentally in THz band [ 18 ], the model shows a decrease in absorption magnitude as the square dimensions (and resonant frequency) decrease, everything else being constant.…”
Section: Resultssupporting
confidence: 85%
“…Using classical transmission line theory and the scattering parameters detected from the VNA, the samples were characterized in terms of absorbance, reflectance, and transmittance. The overall results showed that CNT/PANI composites proved useful for microwave absorption purposes over the Ku-Band in the microwave frequency range (12)(13)(14)(15)(16)(17)(18), with shielding effectiveness up to 28% [4].…”
Section: Cnt Composites In Emi Uses and Microwave Absorption Studiesmentioning
confidence: 95%
See 2 more Smart Citations
“…In all previous efforts [10][11][12] involving both rigid [9,10] and flexible [3,13] substrates, conventional fabrication methods including PCB foundries, screen printing or photolithography based microfabrication have been repurposed to produce metasurfaces from electronic boards, all of which have their challenges. First, the optical properties of the substrate are critical for the metasurface design but, for most conventional large volume uses of PCBs, the manufacturers are more concerned about mechanical and thermal properties, and therefore, the desirable optical properties are not available with most PCB substrates.…”
Section: Introductionmentioning
confidence: 99%